Sciatic Nerve Entrapment from Cerclage Wiring in Intramedullary Nail Fixation - Mohsin Hussein; Ankit Bipin Shah; Bipin Ramanlal Shah; Karthikeyan Parthasarathy Iyengar; Rajesh Botchu (Indian Journal of Radiology and Imaging, 2024)
Cerclage wiring may be used to optimize the stability of intramedullary nail or plate fixations in comminuted proximal femoral fractures, periprosthetic fractures, and other selected cases. In this article, we presented a novel case of iatrogenic sciatic nerve entrapment from cerclage wiring used to supplement intramedullary nail fixation. We also illustrate and highlight the role of ultrasound in assessing the sciatic nerve to make a timely diagnosis.